2015
DOI: 10.1007/s12663-015-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcome of Modified Millard’s Incision and Delaire’s Functional Method in Primary Repair of Unilateral Cleft Lip: A Prospective Study

Abstract: Lip length improvement was better in case of modified Millard's incision. The Delaire's functional method of cleft lip repair results in improved nasal symmetry due to correction of the abnormal insertions of the underlying musculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
7
2
Order By: Relevance
“…According to the assessment based on Steffensen's criteria, the results of the present study proved slightly better than those of Kuna et al 25 , who reported 'good' results in 55.6% of cases for white lip when applying the modified Millard's technique, 66.7% for vermilion using Delaire's technique, 66.7% for scar appearance using Delaire's technique, and 77.8% for the alar base using Delaire's technique.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…According to the assessment based on Steffensen's criteria, the results of the present study proved slightly better than those of Kuna et al 25 , who reported 'good' results in 55.6% of cases for white lip when applying the modified Millard's technique, 66.7% for vermilion using Delaire's technique, 66.7% for scar appearance using Delaire's technique, and 77.8% for the alar base using Delaire's technique.…”
Section: Discussioncontrasting
confidence: 85%
“…The individual assessment of each patient based on Steffensen's criteria showed that lip length was 'good' in 88.1% of cases and 'average' in 11.9% of cases. These results are superior to those of Kuna et al 25 , who reported good results in 66.7% when using the modified Millard technique and 33.3% when using Delaire's technique. Measurement of the distance from the labial commissure to identify Noordhoff's point may lead to the incorporation of deficient tissue during repair 34 .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This difference was statistically significant at P > 0.05. In 2016, A prospective study by Kuna et al; compared the outcomes of Millard and Delaire functional method techniques and found that Millard incision has a better improvement of the lip length, whereas the Delaire method improved nasal symmetry (32) . In 2010; Reddy et al; compared and evaluated nasolabial outcomes (The white roll, vermilion border, scar, Cupid's bow, lip length, nostril symmetry, and appearance of the alar dome and nasal base) between a rotation-advancement repair, Pfeifer wave line incision, and Afroze incision on 1200 patients (22,33) ; where they found that the labial improvement was better with Millard, whereas nasal symmetry was better with Pfeifer incision, and better labial and nasal results with Afroze incision (companion of Millard and Pfeifer) as it improves nasal symmetry, white roll approximation, vermilion repair, scar quality, lip length, and Cupid's bow symmetry by using Millard on medial lip side and Pfeifer on lateral lip side.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, both Millard and Fisher are statistically significant in the increase and improvement of the lateral lip height with better results with Millard technique. Clinically, the lateral lip lengthening of the cleft side was better achieved by Millard's incision because of the use of ''BACK CUT'' which helps in more rotation of flap and overcome vertical lip shortness (32) . In 2017; Mbuyi-Musanzayi et al; evaluated the surgical outcomes of 101 cases using the Fisher technique, the study showed that it increases the length of the medial and lateral lips with a fair scar (34) .…”
Section: Discussionmentioning
confidence: 99%